2001
DOI: 10.1067/mtc.2001.111176
|View full text |Cite
|
Sign up to set email alerts
|

The α folate receptor is highly activated in malignant pleural mesothelioma

Abstract: A majority of mesothelioma tumors examined overexpress the alpha folate receptor protein when compared with normal adjacent tissues. This finding may help explain the observations that antifolate drugs have activity in the treatment of mesothelioma. It also encourages further study of folate receptor-related treatment strategies in this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
75
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 11 publications
2
75
2
Order By: Relevance
“…A review on FRa (Kelemen, 2006) suggests that further research into the presence of FRa in tumours is necessary, as there is a lack of clinical studies using tumour samples, particularly in the context of pemetrexed trials. Until recently, there has been no antibody available to detect FRa by immunohistochemistry in paraffin-embedded tumour samples, although the antibodies Mov18 and Mov19 could be used on frozen sections (Bueno et al, 2001). Another study of FRa in samples of mesothelioma (Khokhar et al, 2002) showed no difference in FRa gene expression (by RT-RNA) in mesothelioma of differing histological type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review on FRa (Kelemen, 2006) suggests that further research into the presence of FRa in tumours is necessary, as there is a lack of clinical studies using tumour samples, particularly in the context of pemetrexed trials. Until recently, there has been no antibody available to detect FRa by immunohistochemistry in paraffin-embedded tumour samples, although the antibodies Mov18 and Mov19 could be used on frozen sections (Bueno et al, 2001). Another study of FRa in samples of mesothelioma (Khokhar et al, 2002) showed no difference in FRa gene expression (by RT-RNA) in mesothelioma of differing histological type.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy for mesothelioma, using pemetrexed and platinum, is now the standard treatment of choice. In mesothelioma, FRa has been described as highly activated (Bueno et al, 2001), with 72% of 61 mesotheliomas showing a two-to four-fold higher mRNA expression compared with normal control tissues. Immunohistochemical studies using Mov 18 and Mov 19 antibodies on frozen sections confirmed the results by demonstrating FRa at the cellular membrane in 13 of 17 samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, hFRα is consistently overexpressed in nonmucinous adenocarcinomas of the ovary, uterus, breast, cervix, kidney, and colon, as well as testicular choriocarcinoma, ependymal brain tumors, malignant pleural mesothelioma, and nonfunctioning pituitary adenocarcinoma (35,44). hFRβ expression is increased in certain leukemias, most consistently seen in chronic myelogenous leukemia and acute myelogenous leukemia (43,45).…”
mentioning
confidence: 99%
“…1 Whereas normal cells rely almost exclusively on the reduced folate carrier (K M for folate 10 25 M) to supply their folate needs, solid tumors of epithelial origin [2][3][4] and hematopoietic cancers of the myeloid lineage 5 frequently overexpress FR (K D for folate 10 210 M) on their cell surfaces, perhaps to enhance their capacity to compete for the vitamin. This upregulation of the high-affinity FR on cancer cell surfaces has rendered the receptor an attractive target for cancer-specific interventions.…”
mentioning
confidence: 99%